Ijtihad Kontemporer Perspektif Yusuf Al-Qardhawi : (Studi Kitab al-Ijtihad fi asy-Syari’ah al-Islamiyyah) - Herdiansyah; Sri Hidayanti; Muannif Ridwan (Jurnal Indragiri Penelitian Multidisiplin, 2022)
This paper examines the contemporary ijtihad methodology from the perspective of a well-known Islamic law expert from the Middle East, Yusuf Al-Qardhawi through his writing entitled Al-Ijtihad fi al-Shari'at al-Islamiah ma'a Nazharat Tahliliyah fi al-Ijtihadi al-Mu. 'ashir (Ijtihad in Islamic Shari'ah: Focus on Contemporary Ijtihad Analysis). The research method used in this paper is a literature review method by directly referring to primary sources with direct analysis of the books written above as well as studies or opinions of other figures regarding the book. In this study it was found that Yusuf Al-Qardhawi offered three contemporary ijtihad concepts, namely, Intiqa'i/tarjihi ijtihad, Insha'i ijtihad, and ijtihad which integrates both Intiqai and Insha'i methods.